Protective Role of Limosilactobacillus fermentum Lf2 and Its Exopolysaccharides (EPS) in a TNBS-Induced Chronic Colitis Mouse Model - Ale, Elisa C.; Irazoqui, Jose Matias; Ale, Analia; Peralta, Guillermo H.; Puntillo, Melisa; Burns, Patricia Graciela; Correa Olivar, Gabriela; Cazenave, Jimena; Bergamini, Carina Viviana; Amadio, Ariel; Binetti, Ana (MDPI, 2024)
Limosilactobacillus fermentum Lf2 (Lf2) is an autochthonous strain that produces high levels of exopolysaccharides (EPS). The objective of this work was to evaluate the probiotic potential of Lf2 and its relationship with these metabolites in a mouse model of TNBS (trinitrobenzene sulfonic acid)-induced chronic colitis. Mice were treated intrarectally with increasing doses of TNBS resuspended in 50% ethanol for 14 days. In parallel, they received different treatments by gavage (lactose 10% as the matrix): freeze-dried Lf2 (L); purified EPS (E); and lactose 10% (T). A healthy control group (H) was treated with 50% alcohol without TNBS (intrarectally) and 10% lactose (by gavage). In the small intestine, there was a significant increase in IgA levels for the group that received EPS and a decrease in IFN-γ for mice treated with the strain compared to the other groups. In the large intestine, IL-2 and IFN-γ presented the lowest levels in the groups treated with EPS and the strain. The concentrations of acetic and propionic acids in mice that received Lf2 were the highest, while the levels of butyric acid were comparable to the healthy control group. An increase in the abundance of SCFA-producing bacteria was observed for mice treated with EPS and the strain in comparison with the colitis control group. The enzyme activity of catalase was higher in all the treatments compared to the TNBS-induced colitis control mice. To summarize the results obtained, a principal component analysis (PCA) was performed, clearly grouping the treatments in different clusters according to the variables studied. This is one of the first studies to address the role of a potential probiotic strain in a chronic colitis mouse model, trying to elucidate the relationship between its properties and the EPS synthesized.